Biological Control Entomopathogenic Nematodes Heterorhabditis sp. and Steinernema sp. Pest Control Termite Land As Coptotermes sp. and Microtermes sp. in The District Lumajang - Qodiriyah Qodiriyah; Didik Sulistyanto; Purwatiningsih Purwatiningsih (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
This research aims to find out the most effective concentration (LC50) and the most effective time (LT50) and to select a biological agent netamoda of nematodes Steinernema sp. dan Heterorhabditis sp. as the environmentally friendly biological control agents on the ground termite Coptotermes sp. and Microtermes sp. in Lumajang. All the data were analyzed by using the termite mortality percentage variance analysis. The LC50 and LT50 were tested by using the probit analysis. Therefore, the empirical probit values were obtained from the percentage of mortality after they were calculated by the Abbot formulation. The biological agents netamoda entomopathogenic Heterorhabditis sp. and Steinernema sp. had the high value on the pathogenicity of Coptotermes sp. and Microtermes sp., the LC50 values on Coptotermes sp. of nematodes Heterorhabditis sp. was 14.94 IJ/ml and Steinernema sp. was 15.22 IJ/ml., the LC50 values on Microtermes sp. of nematodes Heterorhabditis sp. was 16.54 IJ/ml and Steinernema sp. was 20.39 IJ/ml., the LT50 values on Coptotermes sp. of nematodes Heterorhabditis sp. was 1.29 hours and Steinernema sp. was 1.35 hours, and the LT50 values on Microtermes sp. of nematodes Heterorhabditis sp. was 2.14 hours and Steinernema sp. was 1.82 hours. Through pathogenicity test, the entomopathogenic nematodes Heterorhabditis sp. is more effective to control subterranean termites compared with the nematode Steinernema sp. This happens because Heterorhabditis sp. are actively engaged and looking for a host so that there are a large number of possibilities of contacting them with a very large subterranean termites.Keywords: Entomopathogenic nematodes, Heterorhabditis sp., Steinernema sp., LC50, LT50